2020
DOI: 10.3390/f11070724
|View full text |Cite
|
Sign up to set email alerts
|

Global Geographic Distribution and Host Range of Fusarium circinatum, the Causal Agent of Pine Pitch Canker

Abstract: Fusarium circinatum, the causal agent of pine pitch canker (PPC), is currently one of the most important threats of Pinus spp. globally. This pathogen is known in many pine-growing regions, including natural and planted forests, and can affect all life stages of trees, from emerging seedlings to mature trees. Despite the importance of PPC, the global distribution of F. circinatum is poorly documented, and this problem is also true of the hosts within countries that are affected. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 125 publications
1
84
0
Order By: Relevance
“…(Herron et al 2015 ). It has been suggested that these Fusarium species diversified alongside pines in Mexico/Central America (Herron et al 2015 ; O’Donnell et al 1998 ) and that their distribution is driven by international trade, thereby posing significant quarantine risks (Drenkhan et al 2020 ). Availability of genomic resources for these fungi will facilitate and stimulate research aimed at resolving questions regarding their shared evolutionary history, ecology and pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Herron et al 2015 ). It has been suggested that these Fusarium species diversified alongside pines in Mexico/Central America (Herron et al 2015 ; O’Donnell et al 1998 ) and that their distribution is driven by international trade, thereby posing significant quarantine risks (Drenkhan et al 2020 ). Availability of genomic resources for these fungi will facilitate and stimulate research aimed at resolving questions regarding their shared evolutionary history, ecology and pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…One of these corresponds to the so-called “American” clade that was initially proposed to reflect the biogeography of the species it contains (O’Donnell et al 1998 ). For example, Fusarium circinatum , the pine pitch canker pathogen, is thought to be native to Mexico and Central America (Drenkhan et al 2020 ), where it likely co-evolved with its Pinus hosts (Herron et al 2015 ; O’Donnell et al 1998 ; Wikler and Gordon 2000 ). The American clade also includes five additional species associated with Pinus species in Colombia.…”
Section: Introductionmentioning
confidence: 99%
“…The fungus Fusarium circinatum (class Sordariomycetes, phylum Ascomycota) causes pitch canker disease in Pinus species ( 1 , 2 ) and also infects Pseudotsuga menziesii ( 3 , 4 ), maize, and native grasses ( 5 ). This diverse host range and its ability to infect seed have allowed the fungus to spread around the world ( 6 , 7 ). Three isolates (S, V, and LB) collected from Florida, where pitch canker symptoms are prevalent ( 8 ), were selected from eight isolates previously used to inoculate southern pines ( 9 ).…”
Section: Announcementmentioning
confidence: 99%
“…This disease affects conifers, resulting in a serious economic and ecological impact on nurseries and pine stands (Wingfield et al 2008). Since the first report in 1946 in North America, the presence of F. circinatum has been notified in 14 countries of America, Asia, Africa and Europe (Drenkhan et al 2020). The long-distance dispersion as a result of globalization of plant trade and movement of contaminated soil and seed, represents the main pathway for new introductions of the pathogen into disease-free regions (Zamora-Ballesteros et al 2019).…”
Section: Introductionmentioning
confidence: 99%